Mayo Clinic A to Z health guide - Litin, Scott C.; Mayo Clinic (New York, NY : Time Home Entertainment, Inc., 2015)
One of the United States' leading not-for-profit health organizations presents an encyclopedic guide to health that covers such conditions as acne, epilepsy, and lactose intolerance.
Includes index.
Keywords: Health -- Encyclopedias; Medicine, Popular -- Encyclopedias